LOYALITAS KONSUMEN TEPUNG MATA BERAS DIPENGARUHI OLEH KUALITAS LAYANAN MELALUI KEPUASAN KONSUMEN PT. LANDAS NIMPUNA JAKARTA SELATAN - Muhammad Malik Ibrahim Aziz; Edy Sanusi Silitonga (Jurnal Ekonomi dan Industri, 2024)
The purpose of the research is to analyze consumer loyalty which is influenced by service quality through consumer satisfaction with rice flour products of PT. Landas Nimpuna Jakarta Selatan. This research method uses quantitative methods through distributing questionnaires. This study was using the census method. The analysis method uses path analysis. The research results found that: there is an influence of service quality on consumer loyalty, there is an influence of consumer satisfaction on consumer loyalty, there is an influence of service quality on consumer satisfaction, and there is an influence of service quality on consumer loyalty through consumer satisfaction with rice flour products of PT. Landas Nimpuna Jakarta Selatan.